Microservices vs. Monoliths: Comparative Analysis for Scalable Software Architecture Design - Kamisetty, Arjun; Narsina, Deekshith; Rodriguez, Marcus; Kothapalli, Srinikhita; Gummadi, Jaya Chandra Srikanth (Engineering International, 2023)
This research compares monolithic versus microservices architectures for scalable software design. The study reviews the literature on both designs' scalability, development agility, fault isolation, operational complexity, and performance. The results show that monolithic structures are simple and efficient for small applications but struggle with scaling. Microservices provide scalability and flexibility, enabling autonomous scaling and quick development cycles, but they complicate inter-service communication and system integration. Policy implications imply that enterprises should develop explicit architectural governance to choose and deploy software architectures based on application complexity, scalability needs, and team competence. Team training and strong infrastructure are needed to handle microservices' complexity. Software design supports present needs and future development by connecting architectural decisions with strategic goals.